Drip irrigation: Changing the fortune of onion growers - Thangasamy, A; S, Gadge S; Singh, Major (Indian Horticulture, 2019)
Drip irrigation is a potential technology to enhance the yield of onion. Itsaves water and increases the input-use efficiencies. The farmers once startadopting the technology, they become happy by increase in yield withreduced cost of cultivation.